Two new species of the Australian planthopper genus Solonaima Kirkaldy (Hemiptera: Fulgoromorpha: Cixiidae) - Erbe, Petra; Hoch, Hannelore (Zootaxa, 2004)
Two new epigean species of the cixiid genus Solonaima Kirkaldy, which is endemic in eastern Australia, are described from Queensland (Lamington National Park) and New South Wales (Rosebank): S. nielseni n. sp. and S. monteithia n.sp.